Quasiregular mappings of polynomial type in R2 - Fletcher,A; Goodman,D (Conformal Geometry and Dynamics, 2010)
Complex dynamics deals with the iteration of holomorphic functions. As is well known, the first functions to be studied which gave non-trivial dynamics were quadratic polynomials, which produced beautiful computer generated pictures of Julia sets and the Mandelbrot set. In the same spirit, this article aims to study the dynamics of the simplest non-trivial quasiregular mappings. These are mappings in R2 which are a composition of a quadratic polynomial and an affine stretch. © 2010 American Mathematical Society.